THE HABITUATION OF TONGKONAN COMMUNICATION AS ADHESIVES FOR RELIGIOUS HARMONY IN TORAJA PEOPLE - Nurhakki, Nurhakki; Rustan, Ahmad Sultra; Syam, Muhammad Taufiq (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2021)
Religious differences within one family are often found in Toraja society. The four faces of God in one family are a symbol of a family living in harmony and upholding religious tolerance. This study examines how the habituation of communication in maintaining tolerance in building religious harmony in Toraja community is mediated through the existence of Tongkonan (traditional house of Toraja). This study used a qualitative descriptive method in the form of observations, interviews, and focus group discussion (FGD) at three locations which are the research objects, Lembang Madandan, Lembang Kaduaja and Lembang Tombang Langda. The results of this study indicate that a harmonious relationship among religions is a habitus that is built into the mental and cognitive domains that each individual is given freedom to choose religion, is respected (dianggak), is supported in worshiping (diangkak) which is the behavioral internalization of the three main attitudes; sianggak, sikalik, and siangkaran, with Tongkonan as the communication center for collective decision making, problem solving, and conflict resolution. The substance of this research can be used as a reference in realizing religious tolerance through the heritage of local traditions and culture..Keywords: Habitus; Religious Harmony; Tongkonan; Torajaالملخصغالبًا ما توجد الاختلافات الدينية داخل عائلة منطقة واحدة في مجتمع توراجا وجوه رب الأربعة في شرفة واحدة هي تشبيه عائلي حي التناغم والتمسك بالتسامح الديني. تبحث هذه الدراسة في كيفية تعويد التواصل في الحفاظ على التسامح في بناء الانسجام الديني في مجتمع توراجا من خلال وجود تونغكونان (Tongkonan ). استخدمت هذه الدراسة المنهج الوصفي النوعي في شكل الملاحظة والمقابلات ومجموعات التركيز مناقشة (FGD) في موقعين كانا موضع بحث ، مقاطعة ماداندان في شمال توراجا وليمبانج كادواجا ،مقاطعة تانا توراجا. نتائج هذه الدراسة يوضح أن العلاقة المتناغمة بين المعتقدات هي عادة مبنية في المجالات العقلية والمعرفية أن كل فرد يُمنح حرية اختيار الدين ، ويحترم (يحترم) ، ويدعم في ممارسة العبادة (diangka) وهو الاستيعاب لسلوك المواقف الثلاثة الرئيسية : sianggaو sikamalik 'و siangkaran ، مع Tongkonan كمركز في صنع القرار وحل المشكلات وحل النزاعات. يمكن استخدام جوهر هذا البحث كأحد التوصيات.الكلمات الدالة: التعود ، الانسجام الديني, Toraja, Tongkonan ABSTRAKPerbedaan agama dalam satu rumpun keluarga kerap ditemukan di masyarakat Toraja. Empat wajah Tuhan dalam satu beranda, merupakan analogi keluarga yang hidup harmonis dan memegang teguh toleransi beragama. Penelitian ini mengkaji bagaimana habituasi komunikasi dalam menjaga toleransi dalam membangun kerukunan beragama pada masyarakat Toraja yang dimediasi melalui keberadaan Tongkonan. Penelitian ini menggunakan metode deskriptif kualitatif berupa observasi, wawancara, dan focus group discussion (FGD) pada tiga lokasi yang menjadi objek penelitian, Lembang Madandan, Lembang Kaduaja dan Lembang Tombang Langda. Hasil penelitian ini menujukkan hubungan rukun antar keyakinan merupakan habitus yang dibangun dalam ranah mental dan kognitif bahwa setiap individu diberi kebebasan untuk memilih agama, dihargai (diangga’), didukung dalam menjalankan ibadah (diangka’) yang merupakan rinternalisasi dari perilaku tiga sikap pokok; siangga’, sikamalik’, dan siangkaran, dengan Tongkonan sebagai pusat dalam pengambilan keputusan, pemecahan masalah, dan penyelesaian konflik. Substansi penelitian ini dapat dijadikan acuan dalam mewujudkan toleransi beragama melalui warisan tradisi dan budaya lokal.